Effects of PDMS culture on stem cell differentiation towards definitive endoderm and hepatocytes - Clark, Christopher T.; Wang, Yao; Johnson, Devin C.; Lee, Seohyun C.; Smith, Quinton (Acta biomaterialia, 2025)
The generation of human induced pluripotent stem cell (hiPSC) derivatives for regenerative medicine applications holds tremendous promise in treating various disorders. One critical target includes liver disease, in which the primary curative treatment is a cellular transplant aimed to restore the lost function of hepatocytes. In an effort to improve the differentiation of hiPSC-derived liver tissue, we manipulated the mechanical conditions of endoderm specification through directed perturbation of the cytoskeleton and through 2D substrate culture on viscoelastic materials. Through a combination of qRT-PCR, immunofluorescence staining, and functional assays, we found that mechanical cues can bias endoderm specification in an actomyosin and Yes-associated protein (YAP) dependent manner, unveiling new insights into mechanotransduction in germ layer specification and downstream maturation toward parenchymal cells. The translational potential of using human induced pluripotent stem cell (hiPSC) derived hepatocytes to therapeutically improve impaired liver function holds great clinical promise. However, challenges remain in efficiently differentiating functional hepatocytes with mature marker expression. In an effort to improve the differentiation efficiency of hepatocytes, the role of early mechanosensing mechanisms was investigated in the specification of hiPSCs to definitive endoderm progenitor populations. Through a combination of cytoskeletal modulation, control of mechanoresponsive, yes-associated protein expression, and culture on physiologically compliant PDMS substrates, we found that soft environments not only improve progenitor specification but also impact the downstream functionality of differentiated hepatocytes. These results contribute to the collective appreciation that mechanical cues are critical in developmental processes. [Display omitted]